DOCTORAL STUDENTS’ PERSPECTIVES ON ACADEMIC SUPPORT FACTORS: A QUALITATIVE STUDY IN THE DOCTORAL PROGRAM - Hariyati, Nunuk; Riyanto, Yatim; Khamidi, Amrozi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to qualitatively explore doctoral students’ perspectives on the academic support factors that influence the timely completion of their studies in the Doctoral Program in Educational Management at Universitas Negeri Surabaya (UNESA). Method: Employing a phenomenological approach, the study involved many informants, including active students, alumni, and academic supervisors. Data were collected through in-depth, semi-structured interviews, document analysis, and limited observational studies. Results: The findings revealed three main themes: (1) social environment serves as a pillar of emotional and practical support, enhancing students’ academic resilience; (2) learning motivation acts as an internal driving force that maintains commitment and consistency throughout the study process; and (3) self-regulated learning (SRL) reflects students’ academic autonomy in managing time, setting goals, and evaluating their learning progress. These findings highlight that success in doctoral studies is not solely determined by individual capabilities but rather by the dynamic interplay of personal, social, and institutional factors. Novelty: The results of this study are expected to inform academic policymakers in designing strategies to enhance the quality of doctoral education and accelerate students’ study completion in a sustainable and contextually relevant manner.